AN EFFECTIVE TIME MOTION STUDY (TMS) ON OPD PATIENTS OF A TERTIARY CARE HOSPITAL IN SEPTEMBER 2015 IN GOA - Pradipti Verma, Dr. Risha Saxena (International Journal of Research Science and Management, 2015)
The paper is based upon the monitoring the waiting time of patient visiting the Outpatient department of a hospital in Goa using the concept of Time and Motion study. The study was conducted by taking a sample size of 300 patient for a duration of 5 days. The waiting time was found appropriate except the time spend with the doctor. These kind of studies should be carried out as frequently as possible as they give ideas about the need of improvement.